(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The research delved into the geochemical and biogeochemical characteristics of hydromorphic soils within the desert area, focusing on the Yazyavan region as a case study. The primary emphasis was on understanding the pedobiogeochemical aspects of Zinc, particularly its accumulation patterns and anomalies. This investigation developed a framework to quantify both positive and negative anomalies.